(untitled) (Applied Biological Research, 2020)
One hundred and sixty phenotypically superior mahua (Madhuca indica) trees from eastern Madhya Pradesh (India) were intensively assessed for 19 phenotypic traits of mahua tree, flowers and fruits. The correlation and path coefficient of phenotypic traits were established for use in tree improvement of this species. The flower dry weight was found positively and significantly (p<0.01) correlated with flower width (0.69), flower length (0.62) and flower fresh weight (0.55). Fruit and seed characters depicted significant and positive correlation with each other. The residual effect (R) of path analysis indicated that the studied characters contributed to about 73% of flower dry weight. Traits of flower dry and fresh weight, flower width, flower length, fruit weight, seed weight, reducing sugars, crown height and girth at breast height need to be given emphasis in the selection criteria for tree improvement of mahua.